Evaluation of cultured human dermal- and dermo-epidermal substitutes focusing on extracellular matrix components: Comparison of protein and RNA analysis. Issue 3 (May 2017) - Oostendorp, Corien; Meyer, Sarah; Sobrio, Monia; van Arendonk, Joyce; Reichmann, Ernst; Daamen, Willeke F.; van Kuppevelt, Toin H.
Highlights: Quantative evaluation of cellularized skin substitutes to support histology. Biochemical assays were found unsuitable for analysis of ECM proteins. DNA and RNA based methods were found to be reliable and reproducible. Abstract: Treatment of full-thickness skin defects with split-thickness skin grafts is generally associated with contraction and scar formation and cellular skin substitutes have been developed to improve skin regeneration. The evaluation of cultured skin substitutes is generally based on qualitative parameters focusing on histology. In this study we focused on quantitative evaluation to provide a template for comparison of human bio-engineered skin substitutes between clinical and/or research centers, and to supplement histological data. We focused on extracellular matrix proteins since these components play an important role in skin regeneration. As a model we analyzed the human dermal substitute denovoDerm and the dermo-epidermal skin substitute denovoSkin. The quantification of the extracellular matrix proteins type III collagen and laminin 5 in tissue homogenates using western blotting analysis and ELISA was not successful. The same was true for assaying lysyl oxidase, an enzyme involved in crosslinking of matrix molecules. As an alternative, gene expression levels were measured using qPCR. Various RNA isolation procedures were probed. The gene expression profile for specific dermal and epidermal genes could be measured reliably and reproducibly. Differences caused by changes in the cell culture conditions could easily be detected. The number of cells in the skin substitutes was measured using the PicoGreen dsDNA assay, which was found highly quantitative and reproducible. The (dis) advantages of assays used for quantitative evaluation of skin substitutes are discussed.